WHO Drug Information Vol. 27 No. 3 2013. - Organization, World Health (World Health Organization, 2013)
WHO Drug Information communicates pharmaceutical information that is either developed and issued by WHO or transmitted to WHO by research and regulatory agencies throughout the World. The journal also includes regular presentations of newly proposed and recommended International Nonproprietary Names (INN) for Pharmaceuticals Substances. This volume contains the recommended INN List No. 70.